Inositol-requiring enzyme 1α is a key regulator of angiogenesis and invasion in malignant glioma - Auf, Gregor (National Academy of Sciences, 2010)
Inositol-requiring enzyme 1 (IRE1) is a proximal endoplasmic reticulum (ER) stress sensor and a central mediator of the unfolded protein response. In a human glioma model, inhibition of IRE1α correlated with down-regulation of prevalent proangiogenic factors such as VEGF-A, IL-1β, IL-6, and IL-8. Significant up-regulation of antiangiogenic gene transcripts was also apparent. These transcripts encode SPARC, decorin, thrombospondin-1, and other matrix proteins functionally linked to mesenchymal differentiation and glioma invasiveness. In vivo, using both the chick chorio-allantoic membrane assay and a mouse orthotopic brain model, we observed in tumors underexpressing IRE1: (i) reduction of angiogenesis and blood perfusion, (ii) a decreased growth rate, and (iii) extensive invasiveness and blood vessel cooption. This phenotypic change was consistently associated with increased overall survival in glioma-implanted recipient mice. Ectopic expression of IL-6 in IRE1-deficient tumors restored angiogenesis and neutralized vessel cooption but did not reverse the mesenchymal/infiltrative cell phenotype. The ischemia-responsive IRE1 protein is thus identified as a key regulator of tumor neovascularization and invasiveness.